Analysis of Factors Responsible for Poor Patronage of Public Higher Institutions in Nigeria by Competent Foreign Academics - Niyi Jacob Ogunode; Ayoko, Victor Olugbenga; Okechukwu Ezema (International Journal on Integrated Education, 2022)
Academic staff of higher institutions are mobile labour force. The nature of academic job permits them to move from one country to another in search of more satisfactory work experience. Academics migrate from country to country where they carry out teaching, research and community services. Presently, in Nigerian higher institutions especially universities there are few employed foreign academics or lecturers. This paper examines the major factors responsible for poor patronage of competent foreign academics in Nigerian higher institutions. Both qualitative and quantitative data were used in the paper. The literatures were sourced both online and from print materials. It was established that quota system policies, inadequate funding, poor salaries, insecurity, inadequate infrastructural facilities, lack of internationalization policy on higher Education in Nigeria, poor working conditions, unstable academic calendar, poor administration and management model are the factors responsible for the presence of few employed foreign academics in Nigerian higher institutions. The paper recommends that the federal and state government should remove the higher institutions from the federal character employment policy, increase the funding of higher education, increase the salaries of academic staff, provide adequate security and adequate modern infrastructural facilities. Also, the government should come up with internationalization policy on higher education, improve on the working conditions of academic staff and implement all agreement reached with different union groups in the various higher institutions to avoid strike actions.